Brain microenvironment orchestrates highly aggressive tumor variants: current trends and therapeutic approaches - Mishra, Juhi; Dickinson, John D.; Maurya, Shailendra Kumar (Frontiers in Aging Neuroscience, 2025)
Brain tumors exhibit some of the major challenges in the field of oncology owing to their highly heterogeneous, complex, and aggressive nature. The complex anatomy and aggressiveness of the cancer contribute to high mortality and morbidity worldwide. Moreover, the complexity of genetic mutations and dysregulation molecular processes often culminates into treatment resistance. Consequently, brain tumors have become a serious threat to patients’ lives and overall health. Although advancements in the treatment strategies have been made, but the current knowledge amounts to a drop in the ocean, and many patients still struggling with the disease and exhibit poor prognosis. Hence, there is an urgent need to rigorously expand and fasten the ongoing research to address this clinical challenge. This review explores the components of the brain microenvironment that influence tumor homing and progression toward the aggressive phenotype, with the special emphasis on how these pathways could be therapeutically targeted. The complex milieu of brain niche is further amplified by the infiltrating immune cells, which reshape the brain connectome through novel interactions with resident brain cells. We also discuss the different targeted chemotherapeutic, immunotherapeutic, and combinatorial strategies to limit brain metastasis, which currently has limited therapeutic options. Therefore, this review will discuss all the aspects of brain tumor microenvironment (TME), current strategies, and futuristic insights. We will be discussing the individual components of the tumor microenvironment like BBB, stem cells, astrocytes, immune cells, and non-cellular components like ECM. Further, we also shed some light on current therapies and future strategies targeting these microenvironment components.